Clinical efficacy of CO2 fractional laser combined with compound betamethasone in treating vitiligo and its impact on inflammatory factors - Zhang, Lina; Zhang, Jianzhong; Wang, Xin; Zhao, Zhonglin; Li, Zhifeng; Miao, Guoying; Lv, Chao (Frontiers in Medicine, 2024)
Objective: To analyze the clinical efficacy of CO2 fractional laser combined with compound betamethasone in treating vitiligo and its impact on inflammatory factors. Methods: The clinical treatment effects, levels of inflammatory factors [interleukin-17 (IL-17), interferon-gamma (IFN-γ), interleukin-10 (IL-10)], prognosis regarding repigmentation and relapse, psychological health (satisfaction). Results: ① Clinical treatment effects: The total effective rate in Group A was 92.73%, Group B was 74.55%, and Group C was 67.27%, with Group A showing significantly higher effectiveness than Groups B and C (P<0.05). ② Inflammatory factors: Prior to treatment, there was no significant difference in IL-17, IFN-γ, and IL-10 levels among the three groups (P>0.05); after 3 and 6 months of treatment, the levels of IL-17 and IFN-γ decreased significantly while IL-10 levels increased significantly across all three groups, with Group A showing a more pronounced change compared to Groups B and C (P<0.05). ③ Prognosis regarding repigmentation and relapse: After 3 and 6 months of treatment, Group A exhibited significantly higher repigmentation rates compared to Groups B and C (P<0.05); in terms of relapse, Group A had a relapse rate of 5.45%, Group B had 21.82%, and Group C had 23.64%, with Group A showing significantly lower relapse rates compared to Groups B and C (P<0.05). ④ Quality of life and psychological health: At the end of the 6-month follow-up, the quality of life and psychological health of patients in Group A were significantly higher than those in Groups B and C (P<0.05). ⑤ Occurrence of adverse reactions: The incidence of adverse reactions was 12.73% in Group A, 10.91% in Group B, and 9.09% in Group C, with no significant difference observed among the three groups (P>0.05). Conclusion: The application of CO2 fractional laser combined with compound betamethasone in vitiligo patients demonstrates significant efficacy. Compared to sole treatment with CO2 fractional laser or compound betamethasone injections, this combined approach further improves the levels of inflammatory factors in vitiligo patients, reduces the risk of relapse, enhances skin repigmentation, improves quality of life, psychological well-being, without increasing the risk of related adverse reactions. This combined approach merits clinical promotion and application.